(untitled) (Conferencea, 2022)
This work aims to show that an integrated approach to language teaching based on the principles of intercomprehension is applicable to educational institution, on the one hand with regard to the study plan, and on the other hand by adaptation of teaching methods. We have therefore attempted to delineate the pillars of an intercomprehensive approach by examining the concepts of intercomprehension and didactics of languages in order to analyze the English-speaking study plan, the means of teaching English in educational institution and propose ways to adapt the tasks proposed in these resources when necessary.